Code-Mixing Practices of Efl Lecturers in Classroom Settings - Victor, Victor; Pongsapan, Nehru P.; Allo, Markus Deli Girik (Pustaka Digital Indonesia, 2025)
The use of code-mixing in the context of English as a Foreign Language (EFL) instruction has become a common strategy employed by lecturers to bridge linguistic gaps between educators and students. In the Indonesian context, where English is not the primary language, this strategy is considered essential in helping students grasp complex learning materials. This study aims to identify the types of code-mixing used by EFL lecturers and analyze their impact on students’ learning behavior, cognitive abilities, and emotional responses in the classroom. The research employed a qualitative approach using a case study method. Purposive sampling was used to select lecturer participants, while snowball sampling was applied to recruit student participants. The study was conducted at Campus 1 of the Christian University of Indonesia Toraja. Data were collected through classroom observations and in-depth interviews with both lecturers and students. The findings reveal that four types of code-mixing were employed by lecturers: insertion, alternation, congruent lexicalization, and shifts in pronunciation. Overall, the use of code-mixing had positive effects, such as enhancing students’ comprehension of the material, increasing their learning motivation, and creating a more inclusive and comfortable classroom atmosphere. However, the study also identified a potential drawback, students’ growing dependence on lecturers for understanding English, which may hinder their ability to learn independently. These findings highlight the importance of implementing a balanced teaching strategy to ensure that code-mixing serves as an effective instructional aid without diminishing students’ opportunities to develop their language skills autonomously. This research is expected to contribute to the development of more reflective and contextually relevant English teaching practices in higher education.